Chile : Staff Report for the 2005 Article IV Consultation; Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the 2005 Article IV Consultation for Chile highlights short-term economic outlook and fiscal policy under the structural surplus rule. The government is firmly committed to the structural surplus rule. The core inflation rate has risen, reflecting the gradual closing of the output gap and the second-round effects of higher energy prices. The central bank plans to continue gradually withdrawing monetary stimulus. It has appropriately started to raise interest rates, and further increases will likely be needed, depending on developments in inflation and the closing of the output gap.